Effect of Feedstock Powder, Processing Parameters, and Post-Heat Treatment on Cold-Sprayed Cu Alloys: Development of Heterogeneous Material - Eftekhari, Niloofar (University of Waterloo, 2025)
Cold spray (CS) is a solid-state powder deposition technique that utilizes high-velocity impact to bond particles onto a substrate or previously deposited layers in a layer-by-layer approach. This technology is extensively used for repairing high-performance components, protective and functional coatings, and 3D printing applications. However, a major challenge in cold spray additive manufacturing (CSAM) is understanding the relationship between feedstock powder characteristics and the final deposit properties. This thesis focuses on characterizing feedstock powders and analyzing the microstructure, physical properties, and mechanical behavior of cold-sprayed deposits. A key limitation in CS deposited materials is their low ductility. To address this, various strategies, including process optimization and post-deposition heat treatment, are explored to enhance their mechanical properties. Furthermore, a novel approach has been introduced to improve ductility through the fabrication of heterogeneous laminated structures, where alternating layers of hard and soft alloys create a microstructure with fine-grained and coarse-grained regions, ultimately enhancing the mechanical performance of CS deposits. To explore this, the cold-sprayability of various Cu powders produced by electrolysis, gas atomization, and grinding was examined and compared using scanning electron microscopy (SEM), electron backscatter diffraction (EBSD), particle analysis (CAMSIZER, FT4 powder flow tester), and nano-hardness testing. The results indicated that the spherical morphology of gas-atomized powders had a lower surface area compared to the irregular-shaped electrolytic and ground powders, reducing surface interactions and improving powder flowability. Additionally, gas-atomized Cu powders with equiaxed grains exhibited an average nano-hardness value, balancing flowability and deformability. Therefore, these powders were identified as promising feedstock materials for CS applications. Furthermore, the impact of these powders on coating microstructure and mechanical properties was investigated. A comprehensive statistical model was developed to optimize process gas temperature and pressure for deposition. It was found that operating near the upper temperature and pressure limits of the low-pressure cold spray (LPCS) system resulted in coatings with minimal porosity, high flattening ratio, increased microhardness, and enhanced bonding strength. Surface and microstructural evolution analysis revealed that lower oxide content near the surface of more spherical, satellite-free powders significantly enhanced plastic deformation and grain refinement during deposition. Improving the mechanical properties of CS depositions for optimal strength and ductility under uniaxial tensile testing leads to the next step, which involves investigating the effects of different processing gases (Nitrogen and Helium) and post-heat treatment on pure Cu. The findings suggest that while Cu 3D-printed parts processed with He exhibit higher deposition efficiency, N₂-processed samples show greater plastic deformation and lower porosity due to the higher number of deposition passes and the peening effect required to achieve the same thickness as He-processed samples. Heat treatment, when applied at an appropriate temperature and duration, enhances interfacial bonding, promotes recrystallization, and facilitates grain growth, leading to strength and ductility improvements of up to 2.7 times and 28 times, respectively. Heat treatment also plays a critical role in defining the microstructure and mechanical performance of CSAM CuCrZr alloys, an area that remains less explored. The as-sprayed CuCrZr alloy exhibited weakly bonded particle interfaces and porosity, which were significantly reduced by solution annealing and age hardening (SA+AH). This process led to grain reorganization, interfacial healing, solid-state diffusion bonding and precipitation of ultra fine particles resulting in strength and ductility enhancements of up to 2.4 times and 9 times, respectively. Engineering heterogeneous microstructures has emerged as an effective strategy to enhance the mechanical behavior of materials processed through various thermomechanical and manufacturing techniques. However, this approach remains largely unexplored in 3D-printed cold-sprayed components. In this study, a dual heterogeneous laminated Cu/CuCrZr composite structure with varying interface spacing was developed using LPCS followed by post-heat treatment. This tailored microstructure consists of alternating coarse- and fine-grained regions, generating microstructural contrast that induces hetero-deformation-induced (HDI) strengthening. The mechanical incompatibility between the soft Cu and hard Cu-Cr-Zr layers enhances strength and ductility, with decreasing interface spacing improving strength and ductility by up to 10% and 28%, respectively. To further understand the strain hardening mechanisms, loading-unloading-reloading (LUR) experiments and microstructural analyses were conducted. The findings attribute the enhanced mechanical performance to well-bonded particles and HDI strengthening, driven by geometrically necessary dislocations (GNDs) at heterogeneous interfaces. This effect improves work-hardening capacity, leading to simultaneous increases in both strength and tensile ductility of the laminated alloy. While this innovative heterogeneous design strategy for cold-sprayed materials requires further exploration across various topologies, heat treatment methods, and alloy systems, it presents a promising approach to enhancing strength and ductility in low-pressure cold spray materials.
Keywords: cold spray; powder; additive manufacturing; post-heat treatment; heterogeneous microstructure; ductility